The Role of Talent Management in Improving the Quality of Human Resources: A Case Study approach of National Private Companies - Harimurti, Cundo; Hermawan, Rudianto (Technium Social Sciences Journal, 2021)
One of the qualities of a company can be assessed is the quality of its human resources. Therefore, human resources are one of the most valuable company assets, because every employee has talent, skills, knowledge and experience that can make a big contribution to the company in improving the performance of the employees concerned and the continuity of the company that wants employees to work optimally. Human resource management in the company has evolved and experienced changes from Personnel, Human Resources Strategic and Talent Management. This study aims to answer the question of why there are still many national private companies that have not used the Talent Management system and how the application of talent management is to improve the quality of the company’s human resources. This is a qualitative research with a case study approach. Semi-structured interviews were used in data collection. This study shows that Talent Management can increase employee motivation and enthusiasm to work because every employee feels cared for, evaluated on their work and given feedback so that employees can immediately improve their work and can improve the quality of their work performance. Talent Management also does not differentiate between employees. All employees are considered talents and must be developed uniquely because each employee has their own strengths and weaknesses.